ANALYSIS OF PRINCIPLES OF VIBRATIONS REDUCTION OF PIPELINE SYSTEMS FOR OIL AND GAS ENTERPRISES - Іващенко, Василь Трифонович; Слободян, Володимир Іванович; Лях, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Principles and methods of vibrations reduction of technological systems of pipelines and its equipment on oil and gas enterprises are given. The waving processes and its amplitude and frequency characteristics were described. The various methods of vibration reducing and outputting of pipeline system elements of compressor stations from resonance mode are suggested.